The place of ecology in academic performance as perceived by students in Nandi, Kenya. - Yegoh, Ernest; Kiplagat, Paul; Tuimur, Richard (International Journal of Scientific Research in Education, 2016)
This study determined the ecological factors, as perceived by students of high and low achieving schools that contribute to the academic achievement in Nandi Central district. We employed causal comparative research design to identity the cause–effect relationship between school ecology of high and low performing secondary schools. Random sampling technique was employed to select the study participants. There were 424 participants. T-test, a parametric statistical tool was used to compute the mean of the perceptions of students on the aspects of school ecology in both high and low achieving schools. Secondary schools in Nandi–Central district have a generally favorable ecology, as rated by students. The study concludes that low performing schools have a less favorable ecology compared to the high achieving schools. Thus, school ecology significantly influences academic performance in secondary school.
http://www.ijsre.com
Keywords: Kenya; Ecology; Learning Environment; Academic performance; Educational Function; School Administrators